Caracterización de suelos por cromatologia en papel en tres terrazas de banco con sistemas agroforestales del campus CEASA-UTC 2023. - Borja Chanalata, David Joel (2023)
The objective of this work was to characterize the soil using the paper chromatography technique in three bench terraces with agroforestry systems on the Salache campus. For the fulfillment of the objective, 3 crops were taken into account for the sampling, these being alfalfa, fruit trees and forestry, with which the methodology proposed by Restrepo was used, in which we had as results the central zone of the chromatogram with a range of 1, 37 being this which is close to the established range with a light brown color, then it can be said that the soil of the terrace is in the process of compaction and has little aeration, likewise the other zones such as the intermediate zone of the chromatograms where a range favorable is 4.35 then the color is a very light brown with these results we can indicate that it has little or no organic matter. In the external zone is where the microorganisms present in the soil can be found, but the light brown color of our chromas specifies that there are not a large number of microorganisms in the soil. So the results of the soil characterization indicate that the soil is in the process of compaction and aeration is disappearing, the soil also has a large amount of organic matter, but it is not integrated into the soil, which does not help for its recovery, so Chromatography is an economic and feasible analysis that can help to consult the state in which the soil is found. .